MYCN-driven fatty acid uptake is a metabolic vulnerability in neuroblastoma - Ling Tao; Mahmoud A. Mohammad; Giorgio Milazzo; Myrthala Moreno-Smith; Tajhal D. Patel; Barry Zorman; Andrew Badachhape; Blanca E. Hernandez; Amber B. Wolf; Zihua Zeng; Jennifer H. Foster; Sara Aloisi; et al. (Nature Communications, 2022)
Half of high-risk neuroblastoma patients have MYCN amplification. Here, the authors show that MYCN induces fatty acid uptake and synthesis to support neuroblastoma and inhibition of a fatty acid transporter impairs tumor progression in preclinical models.